Effects of Laparoscopic Hyperthermic Perfusion Therapy Combined with Adjuvant Treatment of Compound Yew Capsule on Ovarian Blood Flow Parameters and Immune Function in Patients with Ovarian Cancer. (13th July 2022) - Su, Mengya; Wang, Donghui; Huang, Ping
Abstract : Objective . To determine the effects of laparoscopic hyperthermic perfusion therapy combined with adjuvant compound yew capsules on ovarian blood flow parameters and immune function in patients with ovarian cancer (OC). Methods . A total of 90 OC patients enrolled in our hospital between January 2019 and January 2020 were randomly distributed into the control (Con group) and experimental group (Exp group) based on the sealed envelope method. The Con group was administered laparoscopic hyperthermic perfusion therapy. On this basis, the Exp group was subjected to compound yew capsules; the ovarian blood flow parameters and immune function indexes were compared between the two groups. Results . The Exp group was reported to perform better than the Con group regarding ovarian blood flow parameters and immune indexes after treatment (p < 0.001 ). Conclusion . Laparoscopic hyperthermic perfusion therapy combined with adjuvant compound yew capsules for patients with OC can substantially improve the clinical indexes and immune function. Furthermore, research and adequate promotion are needed to elicit the evidence beyond preclinical studies to understand the intricacies of its implementation.